Different mechanisms contribute to the biphasic pattern of carboxypeptidase U (TAFIa) generation during in vitro clot lysis in human plasma - Leurs, Judith; Wissing, Britt-Marie; Nerme, Viveca; Schatteman, Katinka; Björquist, Petter; Hendriks, Dirk (Thrombosis and Haemostasis, 2003)
Carboxypeptidase U (CPU, TAFIa) recently gained interest as a significant player in dampening the fibrinolytic rate. The aim of this study was to investigate the time course of the generation of CPU activity during coagulation and fibrinolysis using an in vitro clot lysis model in human plasma. A first peak of CPU activity appeared after initiation of the coagulation phase and a second rise in CPU activity was observed during the fibrinolysis. The decrease in the proCPU plasma concentration followed the same trend as the appearance of the CPU activity. The direct thrombin inhibitor inogatran eliminated the CPU generation during coagulation but not during fibrinolysis. Addition of the plasmin inhibitor aprotinin during fibrinolysis resulted in a decrease in CPU activation during the lysis phase. These results demonstrate that proCPU was activated during coagulation by thrombin and during fibrinolysis by plasmin. Addition of a CPU inhibitor before initiation of clotting decreased the clot lysis time as expected. However, addition in the time period between the two peaks of CPU activity had no apparent effect on the clot lysis time.
Keywords: Carboxypeptidase U; TAFI; clot lysis; inogatran; fibrinolysis